2019
DOI: 10.3171/2019.5.peds19126
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy in pediatric stroke: systematic review, individual patient data meta-analysis, and case series

Abstract: OBJECTIVEThe role of mechanical thrombectomy in pediatric acute ischemic stroke is uncertain, despite extensive evidence of benefit in adults. The existing literature consists of several recent small single-arm cohort studies, as well as multiple prior small case series and case reports. Published reports of pediatric cases have increased markedly since 2015, after the publication of the positive trials in adults. The recent AHA/ASA Scientific Statement on this issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 67 publications
2
82
2
3
Order By: Relevance
“…There are several case reports and series of cases on mechanical thrombectomy in children, documenting the efficacy of this technique, as well as its safety, in a similar fashion as in adult patients. 4 , 8 , 10 , 13 , 1621 Presently, several literature reviews and systematic reviews have already been published on thrombectomy in large vessel occlusion pediatric stroke. 2 , 8 , 9 , 11 , 12 , 2225 Table 2 summarizes the largest recent series of cases in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several case reports and series of cases on mechanical thrombectomy in children, documenting the efficacy of this technique, as well as its safety, in a similar fashion as in adult patients. 4 , 8 , 10 , 13 , 1621 Presently, several literature reviews and systematic reviews have already been published on thrombectomy in large vessel occlusion pediatric stroke. 2 , 8 , 9 , 11 , 12 , 2225 Table 2 summarizes the largest recent series of cases in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, some reviews have gathered the published cases of endovascular treatment reported worldwide, and conclude that thrombectomy leads to high recanalization rates in children, similarly to adults, with excellent clinical outcome. 4 , 9 , 10 However, even in reviews, numbers of treated cases are still low, reporting as few as 29 cases in one review of the literature between 2008 and 2015, 9 38 cases in a national database study in the US, representing 1% of the total pediatric ischemic stroke cases, 2 and 44 cases in one review between 1990 and 2016. 11 Despite the published literature, prospective evidence is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“… 35 , 36 Given the emerging literature data supporting the safety and efficacy of MT in childhood stroke treatment, but also the better functional outcomes of conservatively treated pediatric stroke in general compared with adult stroke, larger studies as well as international registries are needed to investigate the potential benefit in pediatric stroke from IVT. 37 Individualized patient management and close collaboration of Pediatricians with stroke specialists is necessary to take decisions regarding IVT administration, particularly for otherwise eligible for IVT pediatric patients, who present with significant neurological deficits within the 4.5 h time window. 38 With regard to the upper age limit of 80 years, the individual patient data meta-analysis of nine RCTs and a recent individual patient data meta-analysis combining both randomized and observational data have provided robust evidence that alteplase for AIS patients aged >80 years has a positive benefit–risk profile when administered according to the other regulatory criteria.…”
Section: Age Limitmentioning
confidence: 99%
“…However, there has been an increasing number of published case reports and case-series describing thrombolysis and endovascular therapy as a feasible and promising treatment option even in very young children. [55][56][57][58][59] The recently published results of the Save ChildS Study, investigating feasibility, safety and outcome of endovascular recanalization of childhood AIS, are encouragingly positive. 60 In this retrospective, multicentrecohort study on 73 children treated in 27 international stroke centres, the safety profile of mechanical thrombectomy was comparable to those in randomized clinical trials for adults and outcome of most of the treated children was favourable.…”
Section: Management Thrombolysis and Mechanical Thrombectomymentioning
confidence: 99%